License Auctions with Royalty Contracts for (Winners and) Losers - Thomas Giebe; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
This paper revisits the licensing of a non-drastic process innovation by an outside innovator to a Cournot oligopoly. We propose a new mechanism that combines a restrictive license auction with royalty licensing. This mechanism is more profitable than standard license auctions, auctioning royalty contracts, fixed-fee licensing, pure royalty licensing, and two-part tariffs. The key features are that royalty contracts are auctioned and that losers of the auction are granted the option to sign a royalty contract. Remarkably, combining royalties for winners and losers makes the integer constraint concerning the number of licenses irrelevant.
urn:nbn:de:bvb:19-epub-13353-0
Keywords: D21; D43; D44; D45; 330; patents; licensing; auctions; royalty; innovation; R&D; mechanism design